Phylogenetic Analyses of Quasars and Galaxies - Fraix-Burnet, Didier; D'Onofrio, Mauro; Marziani, Paola (Frontiers in Astronomy and Space Sciences, 2017)
Phylogenetic approaches have proven to be useful in astrophysics. We have recently published a Maximum Parsimony (or cladistics) analysis on two samples of 215 and 85 low-z quasars (z < 0.7) which offer a satisfactory coverage of the Eigenvector 1-derived main sequence. Cladistics is not only able to group sources radiating at higher Eddington ratios, to separate radio-quiet (RQ) and radio-loud (RL) quasars and properly distinguishes core-dominated and lobe-dominated quasars, but it suggests a black hole mass threshold for powerful radio emission as already proposed elsewhere. An interesting interpretation from this work is that the phylogeny of quasars may be represented by the ontogeny of their central black hole, i.e. the increase of the black hole mass. However these exciting results are based on a small sample of low-z quasars, so that the work must be extended. We are here faced with two difficulties. The first one is the current lack of a larger sample with similar observables. The second one is the prohibitive computation time to perform a cladistic analysis on more that about one thousand objects. We show in this paper an experimental strategy on about 1500 galaxies to get around this difficulty. Even if it not related to the quasar study, it is interesting by itself and opens new pathways to generalize the quasar findings.